Study the Sources of Work Related Stress Risk at Construction Sector of Afghanistan - Zadran, Badam Gul; Haqyar, Fazlurahman; Hamid, Abdul Rahim Abdul (Journal for Research in Applied Sciences and Biotechnology, 2023)
This research was carried out to study the sources of work related Stress risk at the construction sector of Afghanistan. Stress risk is major problem not only in Afghanistan but also all over the world. It is important to ensure that workers can perform best, considering the highly competitive demands and competition of the construction industry. The objectives of this research are to study the sources of work related stress risk at the construction sector of Afghanistan. The methodology of this study includes data collection, and data analysis. Data was collected using questionnaire survey in Afghanistan through email from the construction industry professional such as project manager, site supervisor, project engineer, quantity surveyor, and architect. The data was analyzed using frequency analysis, the average index. To visualize the result, tables, figures like bar, and pie charts were used to clarify the results. The research revealed that the physical environment, the job itself, and the organization is the key factor for the source stress risk at construction industry of Afghanistan. Based on the analysis of likelihood and severity from eighteen fifteen were main sources were in the very high and high stress risk category for the factors such as workload, work pattern, and work environment.